2019
DOI: 10.1088/1361-6463/ab2aba
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid MoS2-gap-mode metasurface photodetectors

Abstract: Two-dimensional molybdenum disulfide (MoS2) featuring atomically thin thickness and unique electronic structure with favorable bandgap has been widely recognized as an attractive new material for the development of the next generation of ultra-compact, light-weight optoelectronic components. In parallel, the recently emerged metasurfaces have demonstrated exceptional controllability over electromagnetic field within ultra-compact subwavelength dimension offering an unprecedented approach to improve the perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recently, the anisotropic Au metasurfaces, [ 211 ] as a novel approach, has been adopted to develop polarization‐sensitive, fast‐response MoS 2 ‐based photodetectors. [ 212 ] While the stripe array shows stronger anisotropy, the large length of the stripe may cause a mismatch between the LSP resonant frequency and the absorption band of 2D materials. To address this issue, micropatterned gratings composed of plasmonic materials were developed (Figure 9d).…”
Section: Modulation Of Optical Anisotropymentioning
confidence: 99%
“…Recently, the anisotropic Au metasurfaces, [ 211 ] as a novel approach, has been adopted to develop polarization‐sensitive, fast‐response MoS 2 ‐based photodetectors. [ 212 ] While the stripe array shows stronger anisotropy, the large length of the stripe may cause a mismatch between the LSP resonant frequency and the absorption band of 2D materials. To address this issue, micropatterned gratings composed of plasmonic materials were developed (Figure 9d).…”
Section: Modulation Of Optical Anisotropymentioning
confidence: 99%
“…Transition metal dichalcogenides (TMDs) have gained significant attention since the discovery of graphene in 2004. TMDs are being investigated as possible options for next-generation optoelectronic and electrical devices due to their distinguished properties, which include atomic thinness, tunable band gap, high mobility, and excellent electronic and optical properties. ,, Molybdenum disulfide (MoS 2 ) is one of the most widely used and investigated 2D TMDs because of its advantages such as strong in-plane carrier mobility, a layer-dependent band gap, high absorption coefficient, and excellent stability. Monolayer MoS 2 is extensively utilized for the fabrication of photodetectors due to particular optical properties which are not found in bulk materials, such as strong-light matter interaction, high mobility (200 cm 2 /V·S), direct band gap, and so on. MoS 2 in a monolayer exhibits a direct band gap of ∼1.8 eV because of quantum confinement, but MoS 2 in bulk has an indirect band gap of ∼1.3 eV. , Wang et al demonstrated a visible–near-infrared (NIR) light detector based on a monolayer MoS 2 /Si heterostructure, showing a detectivity of 10 13 Jones and an ultrafast rise time (∼3 μs) . Zhou et al constructed a MoS 2 /SnSe 2 van der Waals heterostructure-based visible light photodetector with a high responsivity of 9 × 10 3 A/W .…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum and tungsten-based transition metal dichalcogenides (TMDs) monolayer semiconductors are being exhaustively studied as unique systems to develop numerous applications, including electronic/optoelectronic devices, electrocatalysis, spintronics, and novel platforms to study unconventional quantum phenomena. In particular, molybdenum disulfide (MoS 2 ) in the 2H structural phase exhibits remarkable electronic and optoelectronic properties exploited to develop different device configurations, including transistors [1], photodetectors [2,3], photovoltaics [4], singlephoton emitters [5], electrically tunable lightemitters [6] and lasers [7].…”
Section: Introductionmentioning
confidence: 99%